The Impact of Nutritionist-Led Dietary Adjustments on Diabetic Complications: A Review of Recent Findings - Alzamanan, Salem Mesfer; Zabid, Masoud Marzouk Ali; Alyami, Faris Mohammed; Alkulfut, Hadi Hamad Mana; Al Hindi, Ali Ibrahim; Alshahi, Mohammad Saleh; AL Rasheed, Hezam Fahad; Al safhan, Hamad Hussain; Aljubaili, Ammar Hussain; Al-Rubaie, Abbasi Mufleh (Journal of Ecohumanism, 2024)
Diabetes is a chronic condition associated with serious complications, including cardiovascular disease, neuropathy, retinopathy, and kidney dysfunction. While medication and lifestyle changes are central to diabetes management, nutritionist-led dietary adjustments have increasingly demonstrated significant potential in managing and mitigating these complications. This literature review examines recent findings on the impact of nutritionist-directed dietary interventions on diabetes-related complications. Through systematic analysis of studies from the past decade, this review highlights how targeted dietary modifications—such as low-carbohydrate, Mediterranean, and high-fiber diets—implemented by nutritionists contribute to improved patient outcomes. Nutritionists play a critical role in developing personalized dietary strategies, fostering patient adherence, and educating on sustainable lifestyle changes that alleviate diabetic complications. Findings suggest that nutritionist-led interventions improve glycemic control, reduce cardiovascular risks, and support overall health, positioning nutrition counseling as an integral component of diabetes care. However, further research on long-term impacts and diverse patient populations is recommended to validate these findings.